Experimental uncertainty budget for concrete compressive strength test based on a multifactorial analysis (Fracture and Structural Integrity, 2019)
The objective of the study is to introduce an experimental uncertainty budget process for concrete compressive strength test, based on a protocol that incorporates effects of multiple factors significant for the measurement result. The proposed procedure is rather useful for laboratories seeking accreditation according to ISO/IEC 17025, in order to emphasize the contribution of type A uncertainty estimations, rather than relying on type B estimations that are unable to address the correlation between those factors. Two independent experiments were performed. Experiment I is proposed as a simple, suitably designed, reproducibility trial for laboratories performing EN 12390 test method, i.e. when a specified nominal curing age is targeted, following experimental design on multiple uncertainty parameters. A sensitivity analysis was introduced based on a semi-empirical multifactorial regression model (experiment II) for concrete compressive strength as a function of specimen’s curing age and W/C ratio. The present study is an effort towards an integrated and standardized method for experimental, semi-empirical multifactorial regression estimation of the uncertainty budget for the EN 12390 test method, being useful, also, as a baseline for internal quality control programs when adjusted for the specific characteristics of concrete specimens tested by a laboratory.
Keywords: Concrete compressive strength test; Multifactorial model; Type A uncertainty estimation; Sensitivity analysis